Exploring the Effect of Morphological Instruction on Vocabulary Learning among Iranian EFL Learners - Amirali Khoshkhoonejad; Seyyed Farid Khalifelu; Sahabeh Abdipour (Intelektual Pustaka Media Utama, 2016)
Vocabulary knowledge plays a crucial role in academic development and therefore scholastic success (National Reading Panel, 2000). Also, students' vocabulary knowledge expands through a variety of ways. One of the most practicable strategies in vocabulary learning supported by many researchers is using affix knowledge. The purpose of present study is to investigate the effect of morphological instructions on vocabulary learning among Iranian secondary school students. Participants in this study were sixty Iranian secondary school students who were assigned to control group (30) and experimental group (30). A pre-test and post-test comprising two vocabulary tests measuring students’ morphemic analysis of general English words were administered. The data were analyzed using the Independent Sample T-test to determine if there were improvements made in the two measures within each group, and subsequently whether the magnitude of improvement between the two groups were significant. The results indicated that the experimental group outperformed the control group in the process of guessing the meanings of complex words depending on the morphological analysis. Furthermore, the results did not show significant differences between Morphological Relatedness Strategy and Morphological Structure Strategy in terms of students' achievements.